A Note on Convergence of Wilkinson Matrix with Projection Method - Saxena, Vinay (Recent Research in Science and Technology, 2010)
An attempt has made in this paper to describe an efficient method for solving a system of linear equations with non-zero rows, whose coefficient matrix is almost singular or inconsistent. The equation systems containing 4 by 4 Wilkinson matrix as coefficient matrix has been experimented in order to estimate the potential of projection method .The work has been carried out in FORTRAN on new computational facilities. All calculations have been done in double precision. It is found that this method is very efficient, fast converging and less time consuming